Helpdesk Application Design Electronic Medical Record Reporting - Antik Pujihastuti; Eni Efanti (Research and Evidence on Knowledge in Administration and Management — Medical Electronic Data and Information Systems, 2025)
The number of EMR users in RSUP Dr. M.Djamil Padang often occur disorders such as application errors, EMR hank or application can not be opened, employee/user complaints about the problem is not known to have been done. Purpose: This study aims to design a helpdesk application to streamline the reporting of electronic medical record issues, thereby addressing the existing problems. Methods: This study employed a Research and Development (R&D) method. The research was conducted at Dr. M. Djamil Hospital Padang. Data were collected through observations and interviews with two key 2 informants: the head of the Hospital Information System (SIMRS) and one IT staff. A checklist table was also utilized. The application was designed using the waterfall development method. Results: he resulting helpdesk application for electronic medical record (EMR) issues reporting was developed in line with the workflow of the existing EMR reporting process. The helpdesk comprises four main components: user data, report data, problem solving data, and reporting data. Implications: the helpdesk application is necessary to ensure optimal coordination of users and the EMR manager, thereby minimizing the problems that occur. Conclusion: the designed helpdesk application successfully addresses EMR reporting issues that were previously handled manually.